Preparation method of magnesium-based composite hydrogen storage material

By preparing magnesium-based composite hydrogen storage materials, the ball milling and hydrogenation process of Ce-Co-S compounds and magnesium powder are used to solve the problem of poor kinetic performance of magnesium-based hydrogen storage materials, and a hydrogen storage material with excellent hydrogen absorption and release properties at lower temperatures is achieved.

CN119706740APending Publication Date: 2025-03-28YANSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411949662.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The magnesium-based hydrogen storage materials have poor kinetic properties, slow hydrogen absorption and discharge rate, and high hydrogen release temperature, which limits their practical application.

Method used

By dissolving Co(NO3)2 and Ce(NO3)3 in deionized water, adding glucose and NaOH, a Ce-Co precursor was obtained by hydrothermal reaction, and then mixed with sulfur powder to calcinate to obtain Ce-Co-S compound, and finally ball milled and hydrogenated with magnesium powder to prepare a magnesium-based composite hydrogen storage material.

Benefits of technology

The hydrogen release temperature of magnesium-based hydrogen storage materials is significantly reduced, the kinetic properties and catalyst catalytic efficiency are improved, and the practicality of hydrogen storage materials is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706740A_ABST
    Figure CN119706740A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium-based composite hydrogen storage material preparation method, which comprises: dissolving Co (NO3) 2 and Ce (NO3) 3 in deionized water, adding glucose and NaOH, carrying out a hydrothermal reaction to obtain a Ce-Co precursor, mixing the Ce-Co precursor with sulfur powder, calcining to obtain a dandelion-shaped Ce-Co-S compound, carrying out ball milling on the dandelion-shaped Ce-Co-S compound and magnesium powder, and hydrogenating to obtain the magnesium-based composite hydrogen storage material. The preparation method is simple, the process is easy to control, compared with a pure MgH2 hydrogen storage material, the prepared magnesium-based composite hydrogen storage material has the advantages that the hydrogen desorption temperature is remarkably reduced, the dynamic performance is greatly improved, and the catalytic efficiency of a catalyst and the practicability of the hydrogen storage material are remarkably improved; the hydrogen release amount of the magnesium-based composite hydrogen storage material prepared by the preparation method disclosed by the invention can reach 5.45 wt.% at the temperature of 300 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogen storage materials and relates to a method for preparing a magnesium-based composite hydrogen storage material. Background Art

[0002] With the continuous increase of global population and the acceleration of industrialization, human demand for energy is increasing rapidly. However, the depletion of traditional petrochemical energy (such as coal, oil, and natural gas) threatens the stable supply of energy. In addition, the exploitation and utilization of traditional energy will lead to serious environmental pollution problems. In order to reduce dependence on fossil energy and achieve sustainable development, the world is actively promoting the transformation of energy structure and seeking clean, efficient, and renewable energy alternatives. Hydrogen energy is favored as a clean and renewable energy source, but to achieve large-scale application, efficient hydrogen storage and transportation technology is still the main challenge.

[0003] The current hydrogen storage technology is mainly divided into three categories: high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage and solid-state hydrogen storage. Compared with the other two hydrogen storage methods, solid-state hydrogen storage has the advantages of high safety, high hydrogen storage density, strong environmental adaptability and good cycle reversibility. Among them, magnesium-based hydrogen storage materials are favored by researchers because of their high hydrogen storage capacity (7.6wt.%), abundant reserves and low prices; however, the slow hydrogen absorption and desorption rate, poor kinetic performance and high desorption temperature (above 350°C) of pure MgH2 limit its practical application.

[0004] How to improve the kinetic properties of magnesium-based hydrogen storage materials so that they can be used in practice as soon as possible has become a hot topic in the field. Studies have shown that introducing catalysts into MgH2 to construct composite magnesium-based hydrogen storage materials is an effective solution. Catalysts can accelerate the breaking of Mg-H bonds, promote the dissociation of hydrogen molecules, provide channels for H diffusion, inhibit particle agglomeration, and thus reduce the temperature required for MgH2 to absorb and release hydrogen to meet the needs of practical applications.

[0005] Therefore, it is urgent to develop a composite magnesium-based hydrogen storage material that still has excellent hydrogen absorption and desorption properties at lower temperatures. Summary of the invention

[0006] In view of the above technical problems, the present invention aims to provide a method for preparing a magnesium-based composite hydrogen storage material, wherein Co(NO3)2 and Ce(NO3)3 are dissolved in deionized water, glucose and NaOH are added, a Ce-Co precursor is obtained through a hydrothermal reaction, the precursor is mixed with sulfur powder and calcined to obtain a dandelion-shaped Ce-Co-S compound, and then the compound is ball-milled with magnesium powder and hydrogenated to obtain a magnesium-based composite hydrogen storage material. The preparation method of the present invention is simple and the process is easy to control. Compared with pure MgH2 hydrogen storage material, the prepared magnesium-based composite hydrogen storage material has a significantly lower hydrogen desorption temperature and greatly improved kinetic performance, which significantly improves the catalytic efficiency of the catalyst and the practicality of the hydrogen storage material.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a magnesium-based composite hydrogen storage material is carried out in the following steps in sequence:

[0009] S1. Dissolve 8mmolCo(NO3)2 and 4mmolCe(NO3)3 in 40mL deionized water, add 2.4g glucose and 0.2g NaOH, and react at 160-200℃ for 24-48h to obtain Ce-Co precursor;

[0010] S2, placing the Ce-Co precursor and sulfur powder in a porcelain boat respectively, wherein the sulfur powder is placed upstream of the gas path and the Ce-Co precursor is placed downstream of the gas path, and slowly introducing argon gas for calcination to obtain a Ce-Co-S compound;

[0011] S3. Mix the Ce-Co-S compound and magnesium powder and perform ball milling, then hydrogenate in a hydrogen atmosphere, and repeat the ball milling and hydrogenation for 3-5 times to obtain a magnesium-based composite hydrogen storage material.

[0012] As a limitation of the preparation method of the present invention, in step S2, the mass ratio of the Ce-Co precursor to the sulfur powder is 0.15:0.35.

[0013] As another limitation of the preparation method of the present invention, in step S2, the argon gas flow rate is 30-80 sccm.

[0014] As a third limitation of the preparation method of the present invention, in step S2, the calcination is carried out in the following order:

[0015] (a) In the first heating stage, the temperature is raised from room temperature to 400°C at a heating rate of 5-10°C / min and kept at this temperature for 2 h;

[0016] (b) The second heating stage, heating from 400°C to 460°C at a heating rate of 0.1-1°C / min, and keeping the temperature for 2h;

[0017] (c) the third heating stage, heating from 460°C to 500°C at a heating rate of 0.1-1°C / min, and keeping the temperature for 4 hours;

[0018] (d) Cooling stage: cooling to room temperature along with the furnace.

[0019] In the present invention, the calcination process is crucial for the morphology formation of Ce-Co-S compounds. The first heating stage is to heat up from room temperature to 400°C at a faster heating rate. This stage is the preheating stage of Ce-Co precursor and sulfur powder. The purpose of keeping warm for 2 hours is to make the temperature of each part of the material uniform and avoid reaction differences caused by uneven temperature. If the heating rate at this stage is less than 5°C / min, the reaction time will be excessively prolonged. In addition, if the temperature is low (generally below 300°C), the instrument temperature control is inaccurate, which will lead to the occurrence of side reactions. If the heating rate at this stage is greater than 10°C / min, the Ce-Co precursor will be The body grows abnormally, reducing the active sites in the subsequent sulfurization process. In addition, heating too fast will cause the temperature difference between the interior and surface of the Ce-Co precursor to be too large, resulting in obvious differences in grain growth and poor uniformity of the product. Then, the temperature is raised from 400°C to 460°C at a heating rate of 0.1-1°C / min. This stage is the activation stage of sulfur powder. The sublimation temperature of sulfur powder is generally between 440-450°C. The 2h heat preservation is to fully activate the sulfur powder and make the internal and external temperatures uniform. If the heating rate at this stage is less than 0.1°C / min, the reaction time will be unnecessarily prolonged, and even excessive sulfur will be gasified and flow out with the argon gas flow. If the heating rate at this stage is less than 0.1°C / min, the reaction time will be unnecessarily prolonged, and even excessive sulfur will be gasified and flow out with the argon gas flow. When the heating rate is greater than 1℃ / min, the grain growth of the Ce-Co precursor will be affected, resulting in a decrease in the active sites in the subsequent sulfurization process, and the temperature difference between the interior and the surface of the Ce-Co precursor will be too large, resulting in poor product uniformity. Finally, the temperature is raised from 460℃ to 500℃ at a heating rate of 0.1-1℃ / min. At this stage, a large number of sulfide "seeds" have been formed and stabilized, overcoming the problems of high surface Gibbs free energy and instability of the new phase "seeds" when the new phase is generated. The generation rate of sulfides can be accelerated to a certain extent, and the sulfurization reaction can be completed as soon as possible. At this stage, the sulfurization process is hydrothermally generated precursors. On the basis of the prototype, through the difference in diffusion rates of different ions and sulfur element deposition, the compound grows along the dominant crystal plane and gradually forms a "dandelion" shaped Ce-Co-S compound. The 4h insulation is to allow the sulfurization reaction to proceed fully. If the heating rate at this stage is less than 0.1℃ / min, the reaction time will be unnecessarily prolonged. If the target temperature is not raised to the target temperature for a long time, the sublimated sulfur may be lost in large quantities with the argon flow, and sufficient sulfur source cannot be provided at the optimal reaction temperature. If the heating rate at this stage is greater than 1℃ / min, the grains will grow excessively before the optimal temperature reaction is reached, and the product morphology is not ideal.

[0020] As a fourth limitation of the preparation method of the present invention, in step S3, the mass ratio of the Ce-Co-S compound to the magnesium powder is (5-20): (80-95).

[0021] As the fifth limitation of the preparation method of the present invention, in step S3, the ball milling process is: placing stainless steel balls and materials with a ball-to-material ratio of (20-80):1 in a ball mill, and ball milling for 8-44 cycles at a rotation speed of 350-450r / min, and one cycle is: ball milling for 15 minutes, and resting for 15 minutes.

[0022] As the sixth limitation of the preparation method of the present invention, in step S3, the hydrogenation temperature is 300-500°C, the time is 8-14h, and the hydrogen pressure is 1-5MPa.

[0023] In the present invention, the Ce-Co-S compound prepared by the hydrothermal-calcination method exhibits good catalytic effect in the process of hydrogen absorption and desorption of magnesium-based materials, specifically: first, the Ce-Co-S compound presents a "dandelion"-like structure, and the diameter of a single filament is within the range of nanomaterials, which is conducive to its full mixing, embedding and encapsulation with magnesium powder. The Ce-S component and the Co-S component contained in the compound can both play a catalytic role in the process of hydrogen absorption and desorption of magnesium. The 3d electronic structure of Co and the 4f electronic structure of Ce make the interface between Ce and Co have rich charge interactions, which can not only induce Ce to undergo valence state transformation, but also help to achieve strong mechanical coupling to stabilize part of the transition metal Co. The valence state transformation of Ce in the process of hydrogen absorption and desorption is conducive to the formation of catalytically active substances CeH x As a hydrogen diffusion channel, it can accelerate the transmission rate of H2 in MgH2. The stabilized transition metal Co has 3d electrons, which can reduce the energy barrier of intermediate state formation during the dissociation (hydrogen absorption process) and recombination (hydrogen release process) of hydrogen molecules, promote the reaction, and reduce the dehydrogenation temperature of MgH2. The non-metallic element S can combine with Mg to form MgS, and a large number of grain boundaries and hydrogen diffusion channels are generated between MgS and Mg matrix. Therefore, under the synergistic effect of Ce, Co, and S, a large number of grain boundaries and catalytic active sites are formed in the dense magnesium matrix, which improves the hydrogen absorption and desorption capacity of magnesium-based composite hydrogen storage materials.

[0024] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.

[0025] The above technical solution has the following advantages or beneficial effects:

[0026] 1. The Ce-Co-S compound prepared by the hydrothermal-calcination method of the present invention presents a "dandelion"-like structure, and the diameter of a single filament is within the range of nanomaterials, which is conducive to full mixing, embedding and encapsulation with magnesium powder;

[0027] 2. The magnesium-based composite hydrogen storage material prepared by the present invention can release up to 5.45wt.% of hydrogen at 300°C;

[0028] 3. The preparation method of the present invention is simple, the process is easy to control, and it is convenient for industrial application.

[0029] The invention is suitable for preparing magnesium-based composite hydrogen storage materials.

[0030] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of the Ce-Co-S compound prepared in Example 1 of the present invention;

[0032] Figure 2 This is a hydrogen release curve of the magnesium-based composite hydrogen storage material prepared in Example 1 of the present invention at 300°C;

[0033] Figure 3 This is a hydrogen release curve diagram of the magnesium-based composite hydrogen storage material prepared in Example 2 of the present invention at 300°C;

[0034] Figure 4 This is a hydrogen release curve diagram of the magnesium-based composite hydrogen storage material prepared in Example 3 of the present invention at 300°C;

[0035] Figure 5 This is a hydrogen release curve diagram of the magnesium-based composite hydrogen storage material prepared in Example 4 of the present invention at 300°C;

[0036] Figure 6 This is a hydrogen release curve of the magnesium-based composite hydrogen storage material prepared in Example 5 of the present invention at 300°C;

[0037] Figure 7 This is a hydrogen release curve of the magnesium-based composite hydrogen storage material prepared in Comparative Example 1 of the present invention at 300°C;

[0038] Figure 8 This is a hydrogen release curve of the magnesium-based composite hydrogen storage material prepared in Comparative Example 2 of the present invention at 300°C;

[0039] Fig. 9 This is a hydrogen release curve diagram of the magnesium-based composite hydrogen storage material prepared in Comparative Example 3 of the present invention at 300°C;

[0040] Fig.10 This is a hydrogen release curve of the magnesium-based composite hydrogen storage material prepared in Comparative Example 4 of the present invention at 300°C;

[0041] Fig.11 This is a hydrogen release curve of the magnesium-based composite hydrogen storage material prepared in Comparative Example 5 of the present invention at 300°C. DETAILED DESCRIPTION

[0042] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0043] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0044] Example 1

[0045] This embodiment prepares a magnesium-based composite hydrogen storage material, and the preparation process and steps are as follows:

[0046] S1. Weigh 8mmolCo(NO3)2 and 4mmolCe(NO3)3 and dissolve them in 40mL deionized water, then add 2.4g glucose and 0.2g NaOH, and react at 180℃ for 24h to obtain Ce-Co precursor;

[0047] S2. Weigh 0.15g of Ce-Co precursor and 0.35g of sulfur powder and place them in a porcelain boat respectively, wherein the sulfur powder is placed upstream of the gas path and the precursor is located downstream of the gas path. Slowly introduce argon gas and control the argon gas flow rate to 50sccm. Start the heating program, first increase the temperature from room temperature to 400°C at a heating rate of 5°C / min, keep it warm for 2h, then increase the temperature from 400°C to 460°C at a heating rate of 1°C / min, keep it warm for 2h, then increase the temperature from 460°C to 500°C at a heating rate of 1°C / min, keep it warm for 4h, and finally cool it down to room temperature with the furnace to obtain a Ce-Co-S compound.

[0048] S3. Weigh 0.10g Ce-Co-S compound and 0.90g magnesium powder, mix them evenly in a glove box, transfer them to a ball mill, use a Pulverisette6 planetary ball mill to mill, use stainless steel balls, a ball-to-material ratio of 40:1, a rotation speed of 400r / min, and mill for 28 cycles, one cycle is: milling for 15min, rest for 15min, and naturally cool to room temperature after the ball milling; place the ball-milled powder in the sample tube of a PCT tester, hydrogenate it at 400℃ and 3MPa hydrogen pressure for 10h, repeat the ball milling-hydrogenation for 3 times to obtain a magnesium-based composite hydrogen storage material.

[0049] like Figure 1 , is a scanning electron microscope image of the Ce-Co-S compound prepared in Example 1 of the present invention. It can be seen from the image that the Ce-Co-S compound is a clustered nano short wire structure, similar to a "dandelion" shape.

[0050] The magnesium-based composite hydrogen storage material prepared in this example was tested for its hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Figure 2 As shown, at 300 ° C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 4.85wt.% in 10 minutes.

[0051] Example 2

[0052] This embodiment prepares a magnesium-based composite hydrogen storage material, and the preparation process and steps are as follows:

[0053] S1. Weigh 8mmolCo(NO3)2 and 4mmolCe(NO3)3 and dissolve them in 40mL deionized water, then add 2.4g glucose and 0.2g NaOH, and react at 160℃ for 48h to obtain Ce-Co precursor;

[0054] S2. Weigh 0.15g of Ce-Co precursor and 0.35g of sulfur powder and place them in a porcelain boat respectively, wherein the sulfur powder is placed upstream of the gas path and the precursor is located downstream of the gas path. Slowly introduce argon gas and control the argon gas flow rate to 30sccm. Start the heating program, first increase the temperature from room temperature to 400°C at a heating rate of 10°C / min, keep it warm for 2h, then increase the temperature from 400°C to 460°C at a heating rate of 0.5°C / min, keep it warm for 2h, then increase the temperature from 460°C to 500°C at a heating rate of 0.5°C / min, keep it warm for 4h, and finally cool it down to room temperature with the furnace to obtain a Ce-Co-S compound.

[0055] S3. Weigh 0.20g of Ce-Co-S compound and 0.80g of magnesium powder, mix them evenly in a glove box, transfer them to a ball mill, use a Pulverisette6 planetary ball mill to mill, use stainless steel balls, a ball-to-material ratio of 20:1, a rotation speed of 350r / min, and mill for 8 cycles, one cycle is: milling for 15min, rest for 15min, and naturally cool to room temperature after the ball milling; place the ball-milled powder in a sample tube of a PCT tester, hydrogenate it at 300℃ and 5MPa hydrogen pressure for 14h, repeat the ball milling-hydrogenation for 4 times to obtain a magnesium-based composite hydrogen storage material.

[0056] The magnesium-based composite hydrogen storage material prepared in this example was tested for its hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Figure 3 As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 5.01wt.% after 10 min.

[0057] Example 3

[0058] This embodiment prepares a magnesium-based composite hydrogen storage material, and the preparation process and steps are as follows:

[0059] S1. Weigh 8mmolCo(NO3)2 and 4mmolCe(NO3)3 and dissolve them in 40mL deionized water, then add 2.4g glucose and 0.2g NaOH, and react at 200℃ for 32h to obtain Ce-Co precursor;

[0060] S2. Weigh 0.15g of Ce-Co precursor and 0.35g of sulfur powder and place them in a porcelain boat respectively, with the sulfur powder placed upstream of the gas path and the precursor located downstream of the gas path. Slowly introduce argon gas and control the argon gas flow rate to 80sccm. Start the heating program, first increase the temperature from room temperature to 400°C at a heating rate of 8°C / min, keep it warm for 2h, then increase the temperature from 400°C to 460°C at a heating rate of 0.1°C / min, keep it warm for 2h, then increase the temperature from 460°C to 500°C at a heating rate of 0.1°C / min, keep it warm for 4h, and finally cool it down to room temperature with the furnace to obtain a Ce-Co-S compound.

[0061] S3. Weigh 0.15g Ce-Co-S compound and 0.85g magnesium powder, mix them evenly in a glove box, transfer them to a ball mill, use a Pulverisette6 planetary ball mill to mill, use stainless steel balls, a ball-to-material ratio of 80:1, a rotation speed of 450r / min, and mill for 44 cycles, where one cycle is: milling for 15min, rest for 15min, and naturally cool to room temperature after the milling. Place the milled powder in a sample tube of a PCT tester, hydrogenate it at 500℃ and 1MPa hydrogen pressure for 8h, repeat the ball milling-hydrogenation for 5 times to obtain a magnesium-based composite hydrogen storage material.

[0062] The magnesium-based composite hydrogen storage material prepared in this example was tested for its hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Figure 4 As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 4.49wt.% after 10 min.

[0063] Example 4

[0064] This embodiment prepares a magnesium-based composite hydrogen storage material, and the preparation process and steps are as follows:

[0065] S1. Weigh 8mmolCo(NO3)2 and 4mmolCe(NO3)3 and dissolve them in 40mL deionized water, then add 2.4g glucose and 0.2g NaOH, and react at 180℃ for 24h to obtain Ce-Co precursor;

[0066] S2. Weigh 0.15g of Ce-Co precursor and 0.35g of sulfur powder and place them in a porcelain boat respectively, wherein the sulfur powder is placed upstream of the gas path and the precursor is located downstream of the gas path. Slowly introduce argon gas and control the argon gas flow rate to 40sccm. Start the heating program, first increase the temperature from room temperature to 400°C at a heating rate of 5°C / min, keep it warm for 2h, then increase the temperature from 400°C to 460°C at a heating rate of 0.5°C / min, keep it warm for 2h, then increase the temperature from 460°C to 500°C at a heating rate of 0.5°C / min, keep it warm for 4h, and finally cool it down to room temperature with the furnace to obtain a Ce-Co-S compound.

[0067] S3. Weigh 0.05g Ce-Co-S compound and 0.95g magnesium powder, mix them evenly in a glove box, transfer them to a ball mill, use a Pulverisette6 planetary ball mill to mill, use stainless steel balls, a ball-to-material ratio of 50:1, a rotation speed of 350r / min, and mill for 44 cycles, where one cycle is: milling for 15min, rest for 15min, and naturally cool to room temperature after the milling. Place the milled powder in a sample tube of a PCT tester, hydrogenate it at 500℃ and 3MPa hydrogen pressure for 14h, repeat the ball milling-hydrogenation for 3 times to obtain a magnesium-based composite hydrogen storage material.

[0068] The magnesium-based composite hydrogen storage material prepared in this example was tested for its hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Figure 5 As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 5.31wt.% in 5 minutes.

[0069] Example 5

[0070] This embodiment prepares a magnesium-based composite hydrogen storage material, and the preparation process and steps are as follows:

[0071] S1. Weigh 8mmolCo(NO3)2 and 4mmolCe(NO3)3 and dissolve them in 40mL deionized water, then add 2.4g glucose and 0.2g NaOH, and react at 180℃ for 24h to obtain Ce-Co precursor;

[0072] S2. Weigh 0.15g of Ce-Co precursor and 0.35g of sulfur powder and place them in a porcelain boat respectively, wherein the sulfur powder is placed upstream of the gas path and the precursor is located downstream of the gas path. Slowly introduce argon gas and control the argon gas flow rate to 50sccm. Start the heating program, first increase the temperature from room temperature to 400°C at a heating rate of 10°C / min, keep it warm for 2h, then increase the temperature from 400°C to 460°C at a heating rate of 0.2°C / min, keep it warm for 2h, then increase the temperature from 460°C to 500°C at a heating rate of 0.2°C / min, keep it warm for 4h, and finally cool it down to room temperature with the furnace to obtain a Ce-Co-S compound.

[0073] S3. Weigh 0.10g Ce-Co-S compound and 0.90g magnesium powder, mix them evenly in a glove box, transfer them to a ball mill, use a Pulverisette6 planetary ball mill to mill, use stainless steel balls, a ball-to-material ratio of 30:1, a rotation speed of 420r / min, and mill for 22 cycles, one cycle is: milling for 15min, rest for 15min, and naturally cool to room temperature after the ball milling; place the ball-milled powder in the sample tube of a PCT tester, hydrogenate it at 320℃ and 4MPa hydrogen pressure for 10h, repeat ball milling-hydrogenation for 3 times to obtain a magnesium-based composite hydrogen storage material.

[0074] The magnesium-based composite hydrogen storage material prepared in this example was tested for its hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Figure 6 As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 5.45wt.% after 10 min.

[0075] Comparative Example

[0076] In order to explore the effects of different parameters and different compound catalysts in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were conducted. Different magnesium-based composite hydrogen storage materials were prepared in the following comparative examples, as follows:

[0077] Comparative Example 1

[0078] This comparative example prepares MgH2 hydrogen storage material, and the specific preparation process is as follows:

[0079] Weigh 1 g of MgH2 powder in a glove box, transfer it to a ball mill, and use a Pulverisette6 planetary ball mill to mill it. The grinding balls are stainless steel beads, the ball-to-material mass ratio is 40:1, the rotation speed is 350 r / min, and the ball milling time is 22 hours. The ball milling is 15 minutes, and the interval is 15 minutes. After the ball milling is completed, it is naturally cooled to room temperature.

[0080] The MgH2 hydrogen storage material prepared in this comparative example was tested for its hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled magnesium powder was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Table 1. Figure 7 As shown, at 300°C, the amount of hydrogen released by MgH2 is 0.45wt.% in 10 minutes.

[0081] Comparative Example 2

[0082] This comparative example prepares a magnesium-based composite hydrogen storage material similar to that of Example 1, except that in step S1, Ce(NO3)3 is not added, and the remaining steps and parameters are the same as those of Example 1.

[0083] The magnesium-based composite hydrogen storage material prepared in this comparative example was tested for hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Figure 8 As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 3.70wt.% after 30 minutes.

[0084] Comparative Example 3

[0085] This comparative example prepares a magnesium-based composite hydrogen storage material similar to that of Example 1, except that in step S1, Co(NO3)2 is not added, and the remaining steps and parameters are the same as those of Example 1.

[0086] The magnesium-based composite hydrogen storage material prepared in this comparative example was tested for hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Fig. 9 As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 2.81wt.% in 20 minutes.

[0087] Comparative Example 4

[0088] The magnesium-based composite hydrogen storage material prepared in this comparative example is similar to that in Example 1, except that step S2 is not performed, that is, after the Ce-Co precursor is prepared in S1, it is directly ball-milled with magnesium powder and hydrogenated to obtain the magnesium-based composite hydrogen storage material.

[0089] The magnesium-based composite hydrogen storage material prepared in this comparative example was tested for hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Fig.10 As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 1.01wt.% after 60min.

[0090] Comparative Example 5

[0091] In this comparative example, a magnesium-based composite hydrogen storage material similar to that in Example 1 is prepared, except that in step S2, the temperature is not raised in stages during calcination, but directly raised from room temperature to 500° C. at a heating rate of 1° C. / min and kept at this temperature for 4 h.

[0092] The magnesium-based composite hydrogen storage material prepared in this comparative example was tested for hydrogen release performance. In a glove box filled with high-purity argon, 0.2 g of the mixed ball-milled sample was placed in a sample tube of a PCT tester for hydrogen release performance testing. The test results are shown in Figure 2. Fig.11As shown, at 300°C, the amount of hydrogen released by the magnesium-based composite hydrogen storage material is 3.98wt.% after 30 minutes.

[0093] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a magnesium-based composite hydrogen storage material, characterized in that: Follow the steps below in order: S1. Dissolve 8mmolCo(NO3)2 and 4mmolCe(NO3)3 in 40mL deionized water, add 2.4g glucose and 0.2g NaOH, and react at 160-200℃ for 24-48h to obtain Ce-Co precursor; S2, placing the Ce-Co precursor and sulfur powder in a porcelain boat respectively, wherein the sulfur powder is placed upstream of the gas path and the Ce-Co precursor is placed downstream of the gas path, and slowly introducing argon gas for calcination to obtain a Ce-Co-S compound; S3. Mix the Ce-Co-S compound and magnesium powder and perform ball milling, then hydrogenate in a hydrogen atmosphere, and repeat the ball milling and hydrogenation for 3-5 times to obtain a magnesium-based composite hydrogen storage material.

2. The method for preparing a magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In step S2, the mass ratio of the Ce-Co precursor to the sulfur powder is 0.15:0.

35.

3. The method for preparing a magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In step S2, the argon gas flow rate is 30-80 sccm.

4. The method for preparing a magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In step S2, the calcination is carried out in the following order: (a) In the first heating stage, the temperature is raised from room temperature to 400°C at a heating rate of 5-10°C / min and kept at this temperature for 2 h; (b) The second heating stage, heating from 400°C to 460°C at a heating rate of 0.1-1°C / min, and keeping the temperature for 2h; (c) the third heating stage, heating from 460°C to 500°C at a heating rate of 0.1-1°C / min and keeping the temperature for 4 h; (d) Cooling stage: cooling to room temperature along with the furnace.

5. The method for preparing a magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In step S3, the mass ratio of the Ce-Co-S compound to the magnesium powder is (5-20): (80-95).

6. The method for preparing a magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In step S3, the ball milling process is as follows: placing stainless steel balls and materials with a ball-to-material ratio of (20-80):1 in a ball mill, and ball milling for 8-44 cycles at a rotation speed of 350-450 r / min, wherein one cycle is: ball milling for 15 minutes and resting for 15 minutes.

7. The method for preparing a magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In step S3, the hydrogenation temperature is 300-500°C, the time is 8-14h, and the hydrogen pressure is 1-5MPa.